Tantangan Dan Solusi Keamanan Siber Dalam Transaksi E-Commerce - Nia Ramadhani; Muhammad Irwan Padli Nasution (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This article discusses challenges and solutions related to cybersecurity in e-commerce transactions. With the rapid growth of e-commerce, cybersecurity has become a critical issue that needs to be taken seriously. Cybersecurity challenges in e-commerce transactions include threats such as identity theft, malware attacks, phishing attacks, and data breaches. This article identifies and analyzes some of the cybersecurity challenges faced by e-commerce transactions. These challenges include technological infrastructure vulnerabilities, user non-compliance with good security practices, and a lack of effective detection and response systems to evolving threats. Next, this article presents solutions that can be implemented to overcome cyber security challenges in e-commerce transactions. These solutions include implementing strong data encryption, the use of dual authentication, security training for users, proactive threat monitoring and detection, and increased compliance with security standards. In this article, we also discuss the need for collaboration between governments, e-commerce companies and users to create a better security environment. This collaboration involves exchanging information, establishing appropriate policies, and increasing awareness of the importance of cyber security in e-commerce transactions.